Studi Literatur: Pemanfaatan Animaker sebagai Pengembangan Media Pembelajaran Matematika - Diana Rosiyati; Rizqa Ahmadi; Umy Zahroh (Jurnal Didactical Mathematics, 2025)
Learning media plays an important role, especially for students with low abilities who do not know how to think abstractly, as a result the material given by the teacher needs to be visualized in a concrete form. Therefore, education really means that learning media is used so that it becomes a more optimal and meaningful experience for students. The purpose of this writing is to find the effect of using animaker media in learning mathematics. Using the literature study method by carrying out stages starting from collecting references, reviewing theories, and analyzing the objects studied and collecting 10 articles in the past 3 years. Based on the results of the discussion of the literature study that has been reviewed, it is concluded that there is an influence of animaker media in mathematics learning which has an effect on improving numeracy skills, students' understanding of concepts, learning outcomes and media in learning. Social media influences students' interest in learning mathematics.